Promotion of angiogenesis and proliferation cytokines patterns in peritoneal fluid from women with endometriosis. (August 2016) - Rakhila, Halima; Al-Akoum, Mahera; Bergeron, Marie-Eve; Leboeuf, Mathieu; Lemyre, Madeleine; Akoum, Ali; Pouliot, Marc
Highlights: We examined the cytokine contents in peritoneal fluid from endometriotic women. Angiogenic and proliferative factors were increased in endometriosis. An inverse Pearson correlation was observed between pro and anti-angiogenic factors. Effect of fertility only on MDC. Abstract: Studies have long sought specific cytokines that could characterize endometriosis. Either due to variations between study designs regarding the assessment criteria for the cytokine or to low power resulting from small sample size, no factor proved to be sufficiently specific to endometriosis. In other clinical fields, a combination of several markers proved to be more powerful than a single-molecule approach. As well, in the context of endometriosis, simultaneous assessment of several cytokines present in the peritoneal fluid might help in unveiling patho-physiological processes, thus contributing to a better understanding of the condition. Therefore, the objective of this study was to investigate peritoneal fluid cytokines-derived of endometriotic women. For this retrospective case-control study, peritoneal fluid samples were obtained at laparoscopy and assessed by multiplex. Our data showed distinct patterns of peritoneal fluid cytokine concentrations in endometriotic women most notably a marked increase in EGF, FGF-2, IL-1α, MIP-1β, TGFα, PDGF-AA, PDGF-BB, MCP-3, sCD40L, Gro Pan, IL-17α, MDC and Rantes. The overall effect of fertility status revealed a significant difference for only one cytokine, namely MDC. Furthermore, FLT-3L and IP-10 levels were decreased in endometriosis patients, the former in both menstrual cycle phases and the latter in the secretory phase. A significant inverse Pearson correlation ( p < 0.05) was noted between pro-angiogenic cytokines EGF and FGF and the anti-angiogenic cytokine IP-10 in endometriosis patients at stages III–IV and in the secretory phase. These changes may exacerbate the local peritoneal angiogenic and proliferative reaction observed in women with endometriosis, and contributes to its pathophysiology.